Micro-morphological analysis of foliar uptake and retention of airborne particulate matter (PM)-bound toxic metals: implications for their phytoremediation. Issue 7 (9th August 2022) - Gajbhiye, Triratnesh; Pandey, Sudhir Kumar; Malik, Tanzil Gaffar; Kim, Ki-Hyun; Khan, Mohammed Latif
ABSTRACT: While airborne particulate matter (PM) pollution is a serious problem for urban environments, it can be reduced through uptake by plant leaves. In this study, we investigated and compared the uptake of PM-bound toxic metals by different plant species. Enrichment factor (EF) and correlation analyses across different sample types indicated anthropogenic origins of these toxic metals with airborne source signatures. Scanning electron microscopy (SEM) analyses of both leaf surfaces (adaxial and abaxial) suggested that the micro-morphological properties of the leaf surface (e.g. stomata, trichomes, epicuticular wax, and epidermal appendages) control the accumulation of PM and associated metals in plant leaves. Senna siamea leaves showed the most micro-morphological variation as well as the maximum concentration of toxic metals. It was found that foliar uptake of PM-bound toxic metals is affected by leaf surface morphological characteristics. Our results imply that plant speciation strategies can be used to help decrease PM pollution.